2017
DOI: 10.1371/journal.pone.0169290
|View full text |Cite
|
Sign up to set email alerts
|

High Levels of EBV-Encoded RNA 1 (EBER1) Trigger Interferon and Inflammation-Related Genes in Keratinocytes Expressing HPV16 E6/E7

Abstract: Different types of cells infected with Epstein-Barr virus (EBV) can release exosomes containing viral components that functionally affect neighboring cells. Previously, we found that EBV was localized mostly in infiltrating lymphocytes within the stromal layer of cervical lesions. In this study, we aimed to determine effects of exosome-transferred EBV-encoded RNAs (EBERs) on keratinocytes expressing human papillomavirus (HPV) 16 E6/E7 (DonorI-HPV16 HFKs). Lipid transfection of in vitro-transcribed EBER1 molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…14,26 However, some studies have shown that EBV does not reside in the cervical epithelium but rather within infiltrating lymphoid cells adjacent to the tumor epithelium, potentially influencing the microenvironment. 27,28 Although cellular localization of EBV remains contested, previous reports are in agreement that EBV can infect cervical tissues and potentially influence the risk of progression to high-grade cervical lesions and cervical cancer. 15,16,29,30 Our present findings confirm previous studies including a metaanalysis which found that EBV infection was significantly and positively associated with lesion grade in cervical epithelia and was more prevalent in malignant lesions.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…14,26 However, some studies have shown that EBV does not reside in the cervical epithelium but rather within infiltrating lymphoid cells adjacent to the tumor epithelium, potentially influencing the microenvironment. 27,28 Although cellular localization of EBV remains contested, previous reports are in agreement that EBV can infect cervical tissues and potentially influence the risk of progression to high-grade cervical lesions and cervical cancer. 15,16,29,30 Our present findings confirm previous studies including a metaanalysis which found that EBV infection was significantly and positively associated with lesion grade in cervical epithelia and was more prevalent in malignant lesions.…”
Section: Resultsmentioning
confidence: 91%
“…EBV has been shown to be sexually transmitted, and replicates in cervical epithelial cells with eventual shedding . However, some studies have shown that EBV does not reside in the cervical epithelium but rather within infiltrating lymphoid cells adjacent to the tumor epithelium, potentially influencing the microenvironment . Although cellular localization of EBV remains contested, previous reports are in agreement that EBV can infect cervical tissues and potentially influence the risk of progression to high‐grade cervical lesions and cervical cancer …”
Section: Discussionmentioning
confidence: 99%
“…More recently, it was shown that the uptake of EBER1 containing exosomes by dendritic cells, results in the induction of IFN-related genes and inflammation mediated tumorigenesis. This effect was largely dependent on the level of EBER1 released in exosomes 40 . Our preliminary data indicates that exosomes released from EBER1 transfected cells induce cell proliferation 19 .…”
Section: Discussionmentioning
confidence: 95%
“…However, a significant reduction in EBV immediate early (BZLF1, BRLF1) and early (BALF5, BMRF1) gene expression with increased expression of EBER1 was evidenced in HPV+/EBV+ human foreskin keratinocytes (HFK) compared to that in HPV−/EBV+ rafts [ 106 ]. In cervical cells, increased levels of EBER1 may contribute to the transition from inflammation to oncogenesis of HPV-associated cervical cancer by modulating innate immune responses [ 107 ]. In addition, LMP1 reduces the presence of HPV16 with no expression change in the EBNA1 and EBNA2 latent genes, suggesting that EBV latency is favored over lytic replication in HPV16+ cells.…”
Section: Mechanisms Of Hpv/ebv-mediated Cervical Carcinogenesismentioning
confidence: 99%